A hip abduction exercise prior to prolonged standing increased movement while reducing cocontraction and low back pain perception in those initially reporting low back pain. (December 2016) - Viggiani, Daniel; Callaghan, Jack P.
Abstract: Persons who develop low back pain from prolonged standing exhibit increased muscle cocontraction, decreased movement and increased spine extension. However, it is unclear how these factors relate to pain development. The purpose of this study was to use hip abductor fatigue to manipulate muscle activity patterns and determine its effects on standing behaviours and pain development. Forty participants stood for two hours twice, once following a hip abductor fatigue exercise (fatigue), and once without exercise beforehand (control). Trunk and gluteal muscle activity were measured to determine cocontraction. Lumbo-pelvic angles and force plates were used to assess posture and movement strategies. Visual analog scales differentiated pain (PDs) and non-pain developers (NPDs). PDs reported less low back pain during the fatigue session, with females having earlier reductions of similar scale than males. The fatigue session reduced gluteal and trunk cocontraction and increased centre of pressure movement; male and female PDs had opposing spine posture compensations. Muscle fatigue prior to standing reduced cocontraction, increased movement during standing and reduced the low back pain developed by PDs; the timing of pain reductions depended on spine postures adopted during standing.